2023
DOI: 10.1093/bib/bbad065
|View full text |Cite
|
Sign up to set email alerts
|

A review of enzyme design in catalytic stability by artificial intelligence

Abstract: The design of enzyme catalytic stability is of great significance in medicine and industry. However, traditional methods are time-consuming and costly. Hence, a growing number of complementary computational tools have been developed, e.g. ESMFold, AlphaFold2, Rosetta, RosettaFold, FireProt, ProteinMPNN. They are proposed for algorithm-driven and data-driven enzyme design through artificial intelligence (AI) algorithms including natural language processing, machine learning, deep learning, variational autoencod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…Thermal shift assay is one of the standard characterization methods to evaluate the thermodynamic stability of target protein, where T m is defined as the midpoint of temperature during the protein misfolding and aggregating transition. 42,43 Thermal shift analysis emphasized that the fluorescence T m values of P1 and P2 were slightly lower than the turbidity readings at OD 330 that measures insoluble aggregates. This result indicated that the binding of P1 and P2 probes with misfolded proteins occurred earlier than the formation of insoluble aggregates measured by OD 330 (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Thermal shift assay is one of the standard characterization methods to evaluate the thermodynamic stability of target protein, where T m is defined as the midpoint of temperature during the protein misfolding and aggregating transition. 42,43 Thermal shift analysis emphasized that the fluorescence T m values of P1 and P2 were slightly lower than the turbidity readings at OD 330 that measures insoluble aggregates. This result indicated that the binding of P1 and P2 probes with misfolded proteins occurred earlier than the formation of insoluble aggregates measured by OD 330 (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…MIOX is the most important enzyme for GA production via MI, regardless of microbial fermentation and ivBT here. , MIOX has low specific activity and low stability, resulting in a large amount of MIOX and a long reaction time, respectively. Therefore, further improvements of MIOX could focus on (1) discovery of better enzymes, (2) enzyme engineering by rational design, directed evolution, and AI-aided protein engineering, and (3) enzyme immobilization . Further studies on the stability of MIOX and cascade process optimization are underway to further improve the performance of this process.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent reviews focused on structure-based protein design with DL strategies are available, 39,40 as well as a review related to the design of more stable enzymes. 41 These available strategies for structure prediction can be classified depending on the number of input parameters used: those that require the input query sequence, MSA, and set of templates for accurate predictions and those that predict the folded structure based on the input sequence only. Similarly to AF2, the RoseTTAFold (RF) algorithm developed almost at the same time as AF2 requires an MSA and a set of initial templates to make accurate predictions of the folded structure.…”
Section: Application Of Af2 and Other Deep Learning Techniques For Pr...mentioning
confidence: 99%
“…In this section, we aim to provide a brief overview of the most representative techniques developed, and we put special emphasis to those strategies that are particularly relevant for enzyme design. Some recent reviews focused on structure-based protein design with DL strategies are available, , as well as a review related to the design of more stable enzymes …”
Section: Application Of Af2 and Other Deep Learning Techniques For Pr...mentioning
confidence: 99%